Sam Fox library orchestra folio No.5, piano - MILES, Walter E. [et.al] (Sam Fox Pub., 1912)
To a violetnThe CoquettenHayanJune BreezesnCelestinenIn BirdlandnChanson sans parolesnThe little soubrettenSunset lend